Method and device for filling neutron conversion material in semiconductor microstructure groove

The filling of lithium fluoride in the semiconductor microstructure trench by wet centrifugation technology solves the problems of uneven filling and microstructure damage in the prior art, and achieves dense and complete filling and efficient neutron detection.

CN119451286AActive Publication Date: 2025-02-14SHENZHEN UNIV +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510031883.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-02-14
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The prior art is difficult to achieve dense and complete filling of lithium fluoride in semiconductor microstructure trenches, resulting in low detection efficiency and microstructure damage.

Method used

Using the cold state technology route of wet centrifugation, LiF colloidal solution is added to the semiconductor microstructure trench, and lithium fluoride particles are filled into the trench by centrifugation to ensure uniform filling and density.

Benefits of technology

It realizes the dense and complete filling of lithium fluoride without destroying the semiconductor microstructure, improves the neutron detection efficiency and meets the process requirements of MSND chips.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451286A_ABST
    Figure CN119451286A_ABST
Patent Text Reader

Abstract

The invention provides a method and a device for filling a neutron conversion material in a semiconductor microstructure groove, and belongs to the technical field of semiconductors. According to the method, a wet-process centrifugal cold-state technical route is adopted, and on the premise that a semiconductor is not heated, lithium fluoride particles in colloid are filled into a microstructure in a centrifugal mode. And under the action of centrifugal force, the lithium fluoride in the microstructure is compactly and completely filled, so that the process requirements of the MSND chip are met. In the invention, the semiconductor (3) containing the microstructure groove is fixed on the surface of the semiconductor loader (1) through the electrostatic self-adhesive film (2), and the semiconductor (3) is low in density and small in size, so that rolling or displacement caused by flowing of a solution can be avoided; the semiconductor loader (1) is provided with a limiting bayonet (12), and the semiconductor loader (1) and the stand column (41) of the supporting frame (4) are installed in a matched mode through the limiting bayonet (12), so that the semiconductor loader (1) can be fixed, and the semiconductor loader (1) is prevented from rotating or rolling over.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of semiconductor technology, and in particular to a method and a device for filling neutron conversion materials in semiconductor microstructure grooves. Background Art

[0002] Neutrons are uncharged nuclei in the nucleus of atoms that can be released through special nuclear reactions and play an important role in nuclear technology applications, nuclear energy engineering, and scientific research. Neutron detectors refer to radiation detectors that are sensitive to neutrons and are used to measure the physical parameters of neutrons. The performance of neutron detectors is closely related to the interaction between neutrons and the nuclei of the conversion material, and the magnitude of their effects physically gives the upper limit of neutron detection efficiency. Among them, semiconductor-based microstructured neutron detectors (MSND) are based on existing semiconductor processing technology and have the advantages of a mature industrial chain, pure solid-state devices, small size, high detection efficiency, and easy integration. They have become the research focus of solid neutron detectors.

[0003] The outstanding feature of microstructured semiconductor neutron detectors is that microstructured grooves are formed on semiconductors and neutron conversion materials (usually lithium fluoride) are filled in the grooves. On the one hand, the filling amount of neutron conversion materials is greatly increased, which is conducive to improving the probability of neutron interaction and the probability of secondary charged particles. On the other hand, the grooves are generally more than ten microns, and secondary charged particles can easily penetrate the conversion material to reach the silicon detector, which greatly reduces the self-absorption effect of the conversion material on charged particles and improves the detection efficiency of charged particles. The above two aspects technically guarantee the excellent detection performance of microstructured neutron detectors. There are two core processes in the research and development of this type of detector. One is to make grooves that meet the requirements by etching to ensure that the width, depth and surface state meet the design requirements. The second is to fill the neutron conversion material into the groove in an appropriate way to achieve a good filling effect.

[0004] Conventional microstructure lithium fluoride filling technologies include magnetron sputtering, vapor deposition, mechanical pressing, ultrasonic oscillation, low-pressure condensation, and melt immersion. However, practice has shown that these methods have great limitations and cannot meet the filling requirements of lithium fluoride under semiconductor microstructure conditions. Mechanical pressing and ultrasonic oscillation use external force to press the material into the microstructure groove. The main problems are: 1) uneven filling; 2) the characteristic size of the microstructure is more than ten microns, which is difficult to operate finely; 3) the micro-machined silicon wafer is very fragile, and the microstructure can be easily destroyed by external force. Magnetron sputtering and vapor deposition both decompose the lithium fluoride target material first and then deposit it on the material surface. The main problems of these two methods are: 1) suitable for surface treatment, lithium fluoride accumulates on the surface of the silicon wafer and cannot be filled into the microstructure groove; 2) lithium fluoride is highly corrosive after decomposition, which causes serious pollution and corrosion to equipment (such as vacuum chambers, pipes and valves, etc.); 3) low efficiency and low material utilization. Low-pressure condensation and melt immersion require that lithium fluoride be burned to a molten state first. Low-pressure condensation places the silicon wafer above the lithium fluoride vapor and collects lithium fluoride by condensation. Melt immersion directly immerses the silicon wafer into liquid lithium fluoride. The problems with these two methods are: 1) High-temperature operation. The melting point of lithium fluoride is 870°C. The high-temperature environment can easily cause irreversible damage to the silicon wafer, affecting the electrical properties of the silicon wafer; 2) The structure of lithium fluoride after condensation is fluffy and gathers on the surface of the silicon wafer. There is basically no lithium fluoride inside the groove, and there is actually no filling effect; 3) Since the lithium fluoride melt does not wet the silicon wafer, the microstructure groove inserted with the lithium fluoride melt cannot be immersed in the groove. In actual operation, it also gathers on the surface of the groove, and there is no filling effect inside the groove; 4) Due to the sudden cooling and heating process, thermal stress causes the microstructure of the silicon wafer to collapse, and the process cannot be implemented. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a method and device for filling neutron conversion material in semiconductor microstructure grooves. The method and device provided by the present invention can achieve dense and complete filling of lithium fluoride, a neutron conversion material in the microstructure without destroying the semiconductor microstructure, thereby meeting the process requirements of the MSND chip.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for filling a neutron conversion material in a semiconductor microstructure groove, comprising the following steps: A semiconductor containing microstructure grooves is fixed inside a centrifugal container, a LiF colloidal solution is added into the centrifugal container, and centrifugation is performed to obtain a semiconductor in which the microstructure grooves are filled with neutron conversion materials.

[0007] Preferably, the semiconductor is a silicon-based semiconductor; and the width of the microstructure groove is 15-30 μm.

[0008] Preferably, the method for preparing the LiF colloidal solution comprises the following steps: Ultrasonic mixing of LiF nanopowder and alcohol solvent to obtain LiF colloidal solution; The particle size of the LiF nanopowder is 200-400 nm.

[0009] Preferably, the mass concentration of the LiF colloidal solution is 2‰~1%.

[0010] Preferably, the centrifugation is horizontal centrifugation, the centrifugation speed is 3000-4000 rpm, and the time is 8-15 min.

[0011] Preferably, after the centrifugation, the step further comprises: The semiconductor filled with neutron conversion material in the microstructure grooves is transferred into an alcohol solvent and ultrasonicated to remove excess LiF on the semiconductor surface.

[0012] Preferably, after the centrifugation, the step further comprises: The semiconductor filled with the neutron conversion material in the microstructure grooves is repeatedly subjected to the operation of mixing with the LiF colloidal solution and centrifuging.

[0013] The present invention provides a device for filling neutron conversion material in a semiconductor microstructure groove, comprising a semiconductor loader 1, a loading slot 11 is provided on the surface of the semiconductor loader 1, and an electrostatic self-adhesive film 2 is provided on the surface of the loading slot 11; a limit stopper 12 is provided on the edge of the semiconductor loader 1; A support frame 4 supports the semiconductor loader 1 ; the support frame 4 includes a bottom tray 42 and a column 41 vertically arranged at the edge of the bottom tray 42 , and the width of the column 41 matches the size of the limit buckle of the semiconductor loader 1 .

[0014] Preferably, the electrostatic self-adhesive film 2 is made of polyethylene and has a thickness of 0.1 mm.

[0015] Preferably, the bottom tray 42 is made of frosted material.

[0016] The present invention provides a method for filling neutron conversion material in a semiconductor microstructure groove, comprising the following steps: fixing a semiconductor containing a microstructure groove inside a centrifugal container, adding a LiF colloidal solution into the centrifugal container, and centrifuging to obtain a semiconductor filled with a neutron conversion material in the microstructure groove. The present invention adopts a cold state technical route of wet centrifugation, and fills lithium fluoride particles in the colloid into the microstructure by centrifugation without heating the semiconductor. Under the action of centrifugal force, the lithium fluoride in the microstructure is densely and completely filled, meeting the process requirements of the MSND chip, and solving the problem that other methods are not applicable.

[0017] Furthermore, the present invention can use a high-power optical microscope to check whether the semiconductor surface is deposited and aggregated. If the deposition and aggregation are serious, the surface deposited lithium fluoride particles can be removed by ultrasonic oscillation. In addition, multiple rounds of centrifugal filling can be performed according to the total amount of lithium fluoride to be filled and the mass of lithium fluoride filled in a single time.

[0018] The present invention provides a device for filling neutron conversion materials in semiconductor microstructure grooves, comprising a semiconductor loader 1 and a support frame 4 supporting the semiconductor loader 1. In the present invention, the semiconductor containing microstructure grooves can be fixed to the surface of the semiconductor loader 1 through an electrostatic self-adhesive film 2. Since the semiconductor substrate itself has a low density and a small volume, the semiconductor can be effectively prevented from rolling or displacing due to the flow of the solution; the semiconductor loader 1 is provided with a limit bayonet 12, and the limit bayonet 12 is installed in cooperation with the column 41 of the support frame 4 to fix the semiconductor loader 1 and prevent the semiconductor loader 1 from rotating or rolling, and the support frame 4 can conveniently install and disassemble the semiconductor loader 1. Furthermore, the tray 42 of the support frame 4 is made of frosted material, which can effectively prevent the semiconductor loader 1 from adhering to the tray 42 or the bottom of the centrifugal container due to liquid tension. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of assembling a semiconductor loader 1 and an electrostatic self-adhesive film 2; Figure 2 It is a schematic diagram of assembling a semiconductor 3, a semiconductor loader 1 and an electrostatic self-adhesive film 2; Figure 3 It is a structural schematic diagram of the support frame 4; Figure 4 It is a schematic diagram of the assembly of the semiconductor loader 1 and the support frame 4; Figure 5 The figure is a schematic diagram of the overall structure of the assembled flat-bottom centrifuge tube; Figure 6 The figure is a cross-sectional schematic diagram of a flat-bottom centrifuge tube after assembly; Figure 7 This is a SEM image of the silicon wafer after filling in Example 1; Figure 8 This is a SEM image of the silicon wafer after filling in Example 2; Fig. 9 This is the SEM image of the silicon wafer after filling in Example 3. DETAILED DESCRIPTION

[0020] The present invention provides a method for filling a neutron conversion material in a semiconductor microstructure groove, comprising the following steps: A semiconductor containing microstructure grooves is fixed inside a centrifugal container, a LiF colloidal solution is added into the centrifugal container, and centrifugation is performed to obtain a semiconductor in which the microstructure grooves are filled with neutron conversion materials.

[0021] In the present invention, the semiconductor is preferably a silicon-based semiconductor, and more preferably a silicon wafer. In the present invention, the width of the microstructure groove is preferably 15-30 μm; as a specific embodiment of the present invention, the width of the microstructure groove is 15 μm, 20 μm, 25 μm or 30 μm.

[0022] In the present invention, the centrifugal container is preferably a centrifuge tube, and more preferably a flat-bottom centrifuge tube.

[0023] In the present invention, the mass concentration of the LiF colloidal solution is preferably 2‰~1%, more preferably 0.4~0.8%. As a specific embodiment of the present invention, the mass concentration of the LiF colloidal solution is 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%.

[0024] In the present invention, the method for preparing the LiF colloidal solution preferably comprises the following steps: The LiF nanopowder is ultrasonically mixed with an alcohol solvent to obtain a LiF colloidal solution.

[0025] In the present invention, the particle size of the LiF nanopowder is preferably 200-400 nm. In the present invention, the alcohol solvent is preferably anhydrous ethanol and / or isopropanol.

[0026] In the present invention, the power of the ultrasound is preferably 500-1000 W, more preferably 700-800 W; the time is preferably 8-30 min, more preferably 8-15 min.

[0027] After the ultrasonic mixing, the present invention preferably transfers the obtained LiF colloidal solution to a rotor stirrer for continuous stirring for later use.

[0028] In the present invention, the centrifugation is preferably horizontal centrifugation. In the present invention, the centrifugation is preferably high-speed centrifugation; the centrifugation rate is preferably 3000-4000 rpm, the time is preferably 8-15 min, and more preferably 10 min. The present invention preferably uses a horizontal centrifuge for the centrifugation, and the horizontal centrifuge is equipped with a horizontal rotor. As a specific embodiment of the present invention, the model of the centrifuge is TDL-5A. In the present invention, the semiconductor containing microstructure grooves is preferably fixed to the bottom of the centrifugal container. When centrifuging, the centrifugal container is placed horizontally, and the bottom of the centrifugal container is away from the center of the centrifuge. Under the action of centrifugal force, the lithium fluoride in the microstructure is filled in the microstructure groove.

[0029] After the centrifugation, the present invention preferably uses a high-power optical microscope to check whether there is deposition and aggregation on the semiconductor surface. If the deposition and aggregation are serious, the process further includes: transferring the semiconductor filled with neutron conversion material in the microstructure grooves to an alcohol solvent, performing ultrasound to remove excess LiF on the semiconductor surface.

[0030] In the present invention, the alcohol solvent is preferably anhydrous ethanol. In the present invention, the power of the ultrasound is preferably 500-1000W, more preferably 760W, the frequency is preferably 40kHz, and the time is preferably 8-10s. The present invention removes surface deposited lithium fluoride particles by short-time ultrasonic oscillation.

[0031] After the centrifugation, the present invention preferably calculates the total amount of lithium fluoride filled as needed and the mass of lithium fluoride filled in a single time, and performs multiple rounds of centrifugal filling. In the present invention, the multiple rounds of centrifugal filling specifically include: repeatedly mixing the semiconductor filled with neutron conversion material in the microstructure groove with the LiF colloidal solution-centrifugation operation. The present invention has no special requirements for the number of repetitions, and the total amount of lithium fluoride filled as needed and the mass of lithium fluoride filled in a single time can be calculated accordingly. As a specific embodiment of the present invention, the number of repetitions is 1 time, 2 times or 3 times.

[0032] In the present invention, the specific process of preparing the LiF colloidal solution and centrifuging is the same as above and will not be repeated here.

[0033] After the centrifugation, the semiconductor with the neutron conversion material filled in the microstructure grooves is preferably dried. In the present invention, the drying method is preferably oven drying.

[0034] The present invention provides a device for filling neutron conversion material in a semiconductor microstructure groove, comprising a semiconductor loader 1, a loading slot 11 is provided on the surface of the semiconductor loader 1, and an electrostatic self-adhesive film 2 is provided on the surface of the loading slot 11; a limit stopper 12 is provided on the edge of the semiconductor loader 1; A support frame 4 supports the semiconductor loader 1 ; the support frame 4 includes a bottom tray 42 and a column 41 vertically arranged at the edge of the bottom tray 42 , and the width of the column 41 matches the size of the limit buckle of the semiconductor loader 1 .

[0035] In the present invention, the loading slot 11 on the surface of the semiconductor loader 1 is preferably a hollow structure, and the electrostatic self-adhesive film 2 is adhered to the bottom surface of the semiconductor loader 1 so that the surface of the loading slot 11 is exposed to the electrostatic self-adhesive film 2 .

[0036] In the present invention, the surface of the semiconductor loader 1 is preferably provided with one or more loading slots 11, and the number of the loading slots 11 is preferably 1 to 4. In the present invention, the size of a single loading slot 11 is preferably 1×1 (cm). In the present invention, the shape of the semiconductor loader 1 is preferably the same as the cross-sectional shape of the centrifugal container, and the size is slightly smaller than the cross-sectional size of the centrifugal container 5. The present invention does not make special requirements on the material of the semiconductor loader 1.

[0037] In the present invention, the material of the electrostatic self-adhesive film 2 is preferably polyethylene, and the thickness is preferably 0.1-0.2 mm, more preferably 0.1 mm.

[0038] In the present invention, the size of the bottom tray 42 is preferably the same as that of the semiconductor loader 1. In the present invention, the bottom tray 42 is preferably made of frosted material. As a specific embodiment of the present invention, the material of the bottom tray 42 is aluminum alloy, and the frosted roughness Ra is preferably 1.5-3 μm.

[0039] In the present invention, the number of the columns 41 is preferably 2 to 4; the height of the columns 41 is preferably the same as the height of the centrifugal container.

[0040] In the present invention, a fixing structure 43 is preferably provided above the pillars 41 for connecting and fixing a plurality of pillars 41 and facilitating grabbing for installation and unloading.

[0041] The device for filling neutron conversion material in semiconductor microstructure grooves provided by the present invention also preferably includes a centrifugal container 5, and the centrifugal container 5 is preferably a flat-bottom centrifuge tube. In the present invention, when the semiconductor microstructure grooves are filled with neutron conversion material, the semiconductor 3 is bonded to the surface of the loading slot 11 of the semiconductor loader 1 through the electrostatic self-adhesive film 2, and the semiconductor loader 1 loaded with the semiconductor 3 is engaged with the column 41 through the limit bayonet 12 and fixed to the surface of the bottom tray 42 of the support frame 4. The assembled semiconductor loader 1 and the support frame 4 are placed in the centrifugal container 5 and centrifuged.

[0042] As a specific embodiment of the present invention, the assembly diagram of the semiconductor loader 1 and the electrostatic self-adhesive film 2 is shown in FIG. Figure 1 As shown; the semiconductor 3, the semiconductor loader 1 and the electrostatic self-adhesive film 2 are assembled as shown Figure 2 As shown; the structural schematic diagram of the support frame 4 is as shown Figure 3 As shown; the assembly diagram of the semiconductor loader 1 and the support frame 4 is shown Figure 4 As shown; the overall structure diagram of the assembled flat-bottom centrifuge tube is as shown Figure 5 As shown; the cross-sectional diagram of the assembled flat-bottom centrifuge tube is as shown Figure 6 shown. Figures 1 to 6In the figure, 1 is a semiconductor loader, 2 is an electrostatic self-adhesive film, 3 is a semiconductor, 4 is a support frame, 5 is a centrifugal container, 11 is a loading slot, 12 is a limit stopper, 41 is a column, 42 is a bottom tray, and 43 is a fixed structure.

[0043] The method and device for filling neutron conversion material in semiconductor microstructure grooves provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0044] Example 1 Taking silicon wafer as the semiconductor material, the semiconductor loader corresponds to a silicon wafer loader.

[0045] The loading method of the silicon wafer is as follows: the electrostatic self-adhesive film 2 is adhered to the bottom surface of the semiconductor loader 1, and it is confirmed that there are no bubbles remaining at the bonding point, and the silicon wafer (semiconductor 3) is gently placed in the loading slot 11, and the silicon wafer loader obtained in the above steps is inserted into the columns 41 around the support frame 4 through the limit bayonet 12, and is placed on the bottom tray 42 of the support frame 4, and the support frame 4 obtained in the above steps is placed in a flat-bottom centrifuge tube (centrifuge container 5). After the above steps, a flat-bottom centrifuge tube loaded with silicon wafers is obtained.

[0046] The filling method of LiF powder adopts the following steps: 1) Preparation of LiF colloidal solution: Pour 100 parts of anhydrous ethanol as the main material into a clean beaker, add 0.2 parts of LiF nanopowder with a particle size of 200-400 nm, seal the beaker and place it in an ultrasonic water bath, ultrasonically vibrate at 750W for 30 min, stop ultrasonicating when there is no obvious particle agglomeration in the solution, and obtain LiF colloidal solution, which is then transferred to a rotor mixer and continuously stirred for standby use; 2) High-speed centrifugation: 50 g of the above-mentioned LiF colloidal solution was transferred to a flat-bottom centrifuge tube, and the obtained flat-bottom centrifuge tube was transferred to a centrifuge, and the centrifugal speed was set to 4000 rpm for 10 min. After the centrifuge completes the centrifugal operation, a silicon wafer with preliminary filling was obtained; 3) Ultrasonic cleaning: Pour 10 parts of anhydrous ethanol into a clean beaker, transfer the silicon wafer filled by centrifugation into the anhydrous ethanol solution, place the beaker in an ultrasonic water bath, and perform ultrasonic oscillation for 10 seconds at an ultrasonic power of 760W and a frequency of 40kH to remove the LiF particles deposited on the surface of the silicon wafer; 4) Natural drying: After the ultrasonic cleaning is completed in the above steps, the silicon wafer is taken out and placed in a dryer for natural drying to obtain a filled silicon wafer.

[0047] Example 2 The silicon wafer was loaded in the same manner as in Example 1.

[0048] The filling method of LiF powder adopts the following steps: 1) Preparation of LiF colloidal solution: Pour 100 parts of anhydrous ethanol as the main material into a clean beaker, add 0.5 parts of LiF nanopowder with a particle size of 200-400 nm, seal the beaker and place it in an ultrasonic water bath, ultrasonically vibrate at 750W for 30 min, stop ultrasonication when there is no obvious particle agglomeration in the solution, and obtain LiF colloidal solution, which is then transferred to a rotor mixer and continuously stirred for standby use; 2) High-speed centrifugation: 50 g of the above-mentioned LiF colloidal solution was transferred to a flat-bottom centrifuge tube, and the obtained flat-bottom centrifuge tube was transferred to a centrifuge, and the centrifugal speed was set to 4000 rpm for 10 min. After the centrifuge completes the centrifugal operation, a silicon wafer with preliminary filling was obtained; 3) Ultrasonic cleaning: Pour 10 parts of anhydrous ethanol into a clean beaker, transfer the silicon wafer filled by centrifugation into the anhydrous ethanol solution, place the beaker in an ultrasonic water bath, and perform ultrasonic oscillation for 10 seconds at an ultrasonic power of 760W and a frequency of 40kH to remove the LiF particles deposited on the surface of the silicon wafer; 4) Natural drying: After the ultrasonic cleaning is completed in the above steps, the silicon wafer is taken out and placed in a dryer for natural drying to obtain a filled silicon wafer.

[0049] Example 3 The silicon wafer was loaded in the same manner as in Example 1.

[0050] The filling method of LiF powder adopts the following steps: 1) Preparation of LiF colloidal solution: Pour 100 parts of anhydrous ethanol as the main material into a clean beaker, add 1 part of LiF nanopowder with a particle size of 200-400 nm, seal the beaker and place it in an ultrasonic water bath, and ultrasonically vibrate at 750W for 30 min. When there is no obvious particle agglomeration in the solution, stop ultrasonication to obtain LiF colloidal solution, and transfer it to a rotor mixer for continuous stirring for standby use; 2) High-speed centrifugation: 50 g of the above-mentioned LiF colloidal solution was transferred to a flat-bottom centrifuge tube, and the obtained flat-bottom centrifuge tube was transferred to a centrifuge, and the centrifugal speed was set to 4000 rpm for 10 min. After the centrifuge completes the centrifugal operation, a silicon wafer with preliminary filling was obtained; 3) Ultrasonic cleaning: Pour 10 parts of anhydrous ethanol into a clean beaker, transfer the silicon wafer filled by centrifugation into the anhydrous ethanol solution, place the beaker in an ultrasonic water bath, and perform ultrasonic vibration for 10 seconds to remove the LiF particles deposited on the surface of the silicon wafer; 4) Natural drying: After the ultrasonic cleaning is completed in the above steps, the silicon wafer is taken out and placed in a dryer for natural drying to obtain a filled silicon wafer.

[0051] The filled silicon wafer was placed under an optical microscope for observation, with the eyepiece magnification fixed at 10X. The deposition on the silicon wafer surface was observed at 10X, 20X, and 50X respectively. The silicon wafer was further split along the vertical direction of the etching groove by a splitting method. The side profile of the etching groove of the silicon wafer was observed by a scanning electron microscope (SEM) to evaluate the key parameters such as the filling amount, filling uniformity, and filling density of LiF. The SEM image of the filled silicon wafer in Example 1 is as follows: Figure 7 As shown, the SEM image of the silicon wafer after filling in Example 2 is as follows Figure 8 As shown, the SEM image of the silicon wafer after filling in Example 3 is as follows Fig. 9 shown.

[0052] The mass concentration of the LiF colloidal solution in Example 1 is 0.2%. SEM observation of the side profile of the silicon wafer shows that the LiF is densely filled with a good filling effect, a filling amount of about 50%, and a high filling uniformity.

[0053] The mass density of the LiF colloidal solution in Example 2 is 0.5%. SEM observation of the side profile of the silicon wafer shows that the LiF is densely filled with a good filling effect, a filling amount of about 20%, and good filling uniformity.

[0054] The mass density of the LiF colloidal solution in Example 3 is 1%. SEM observation of the side profile of the silicon wafer shows that the filling effect is poor, the filling amount is about 2%, and the filling uniformity is average.

[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for filling a neutron conversion material in a semiconductor microstructure groove, characterized in that: The following steps are involved: A semiconductor containing microstructure grooves is fixed inside a centrifugal container, a LiF colloidal solution is added into the centrifugal container, and centrifugation is performed to obtain a semiconductor in which the microstructure grooves are filled with neutron conversion materials.

2. The method according to claim 1, characterized in that The semiconductor is a silicon-based semiconductor; the width of the microstructure groove is 15-30 μm.

3. The method according to claim 1, characterized in that The preparation method of the LiF colloidal solution comprises the following steps: Ultrasonic mixing of LiF nanopowder and alcohol solvent to obtain LiF colloidal solution; The particle size of the LiF nanopowder is 200-400 nm.

4. The method according to claim 1 or 3, characterized in that: The mass concentration of the LiF colloidal solution is 2‰~1%.

5. The method according to claim 1, characterized in that The centrifugation is horizontal centrifugation, the speed of the centrifugation is 3000-4000 rpm, and the time is 8-15 min.

6. The method according to claim 1, characterized in that The centrifugation also includes: The semiconductor filled with neutron conversion material in the microstructure grooves is transferred into an alcohol solvent and ultrasonicated to remove excess LiF on the semiconductor surface.

7. The method according to claim 1, characterized in that The centrifugation also includes: The semiconductor filled with the neutron conversion material in the microstructure grooves is repeatedly subjected to the operation of mixing with the LiF colloidal solution and centrifuging.

8. A device for filling neutron conversion material in a semiconductor microstructure groove, characterized in that: It comprises a semiconductor loader (1), wherein a loading slot (11) is provided on the surface of the semiconductor loader (1), and the surface of the loading slot (11) contains an electrostatic self-adhesive film (2); and a limit stopper (12) is provided on the edge of the semiconductor loader (1); A support frame (4) supporting the semiconductor loader (1); the support frame (4) comprises a bottom tray (42) and a column (41) vertically arranged at the edge of the bottom tray (42), the width of the column (41) being consistent with the size of the limiting buckle of the semiconductor loader (1).

9. The device according to claim 8, characterized in that The electrostatic self-adhesive film (2) is made of polyethylene and has a thickness of 0.1-0.2 mm.

10. The device according to claim 8, characterized in that The bottom tray (42) is made of frosted material.

Citation Information

Patent Citations

  • AlGaAs / GaAs neutron detector with PIN microstructure

    CN112490318A

  • Groove rod, silicon wafer boat and silicon wafer boat manufacturing method

    CN113937040A

  • Semi-insulating GaAs micro-groove neutron detector filled with 6LiF

    CN213905378U

  • Experimental centrifugal tube convenient to clean and having anti-sticking function

    CN215353527U

  • Product loading mechanism for high-speed refrigerated centrifuge

    CN220461009U